Long non-coding RNA FTH1P3 facilitates oral squamous cell carcinoma progression by acting as a molecular sponge of miR-224-5p to modulate fizzled 5 expression - Zhang, Chen-Zheng (Gene, 2017)
A growing body of evidence has indicated that long non-coding RNAs (lncRNAs) function as competing endogenous RNAs (ceRNAs) during tumorigenesis. In this study, the qRT-PCR results revealed that the lncRNA ferritin heavy chain 1 pseudogene 3 (FTH1P3) was over-expressed in oral squamous cell carcinoma (OSCC) and decreased the survival rate of OSCC patients. Ectopic expression of FTH1P3 facilitates cell proliferation and colony formation in OSCC cells. Moreover, FTH1P3 acted as a competitive endogenous RNA (ceRNA), effectively becoming sponge for miR-224-5p and thereby modulating the expression of fizzled 5. Importantly, expression analysis revealed that both FTH1P3 and fizzled 5 were up-regulated in OSCC cell lines and tissues, and over-expression of fizzled 5 also functioned as an oncogene in OSCC cells. Our data demonstrated FTH1P3 facilitated OSCC progression by acting as a molecular sponge of miR-224-5p to modulate fizzled 5 expression. Thus, targeting the ceRNA network referring FTH1P3 may be a therapeutic target for treatment of OSCC. •FTH1P3 is up-regulated in human primary OSCC tissues.•Expression of fizzled 5 is up-regulated in primary human OSCC and negatively expressed related to miR-224-5p.•miR-224-5p inhibits the tumorigenic potential of OSCC cells by down-regulating oncogenic FZD5 gene.•FTH1P3′s oncogenic functions are partially through reverse regulation of miRNA-224-5p, and then activation of fizzled 5.